2019
DOI: 10.2147/ott.s216146
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dual targeting of estrogen receptor α and estrogen-related receptor α: a novel endocrine therapy for endometrial cancer</p>

Abstract: BackgroundEndometrial cancer (EC) is a hormone dependent carcinoma that may involve complex molecular mechanisms. Endocrine therapy by blocking the estrogen and estrogen receptor α (ERα) has been effective in breast cancer, while it is still controversial in EC. Recently, estrogen-related receptor α (ERRα) was proven to be another endocrine therapy target.MethodsThe anti-tumor effect of selective estrogen receptor modulators (SERMs) and XCT790 (XCT) used alone or in combination were evaluated in both of ERα-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The SERD fulvestrant/faslodex (Table 2) has been investigated as a treatment for endometrial cancer in phase I/II trials, although well-tolerated, it has low oral bioavailability and further trials are needed (Bogliolo et al 2017). Another recent study suggested dual targeting of ERα with tamoxifen and ERRα with XCT790 may be beneficial for EC treatment, but this requires further validation (Mao et al 2019). While administration of SERMs/SERDs may be appropriate for postmenopausal women with cancer, their use in younger women with non-malignant endometrial disorders such as endometriosis is more challenging with data limited to promising results in preclinical models (Kulak et al 2011, Khine et al 2018.…”
Section: Targeting Oestrogen Receptors In Endometrial Disordersmentioning
confidence: 99%
“…The SERD fulvestrant/faslodex (Table 2) has been investigated as a treatment for endometrial cancer in phase I/II trials, although well-tolerated, it has low oral bioavailability and further trials are needed (Bogliolo et al 2017). Another recent study suggested dual targeting of ERα with tamoxifen and ERRα with XCT790 may be beneficial for EC treatment, but this requires further validation (Mao et al 2019). While administration of SERMs/SERDs may be appropriate for postmenopausal women with cancer, their use in younger women with non-malignant endometrial disorders such as endometriosis is more challenging with data limited to promising results in preclinical models (Kulak et al 2011, Khine et al 2018.…”
Section: Targeting Oestrogen Receptors In Endometrial Disordersmentioning
confidence: 99%
“…Guo found dramatic increases in lipid biosynthesis and lipid peroxidation in a genetically engineered mouse model of endometrioid adenocarcinoma 22 , suggesting that lipidomic changes or reprogramming are signi cant in EC. Previous studies have con rmed that downregulation of ERRα provides a potential therapeutic strategy and inhibits cellular metastasis and invasion in EC 11,25 . However, the mechanism by which ERRα regulates FA and GP synthesis was unexplored prior to our study.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, ERRα-mediated signaling pathways have recently emerged as key factors in the regulation of cancer lipid metabolism. In our previous work, the translational factor activity of TFEB was affected by the downregulation of ERRα expression in EC according to a high-throughput DNA/protein assay 25 , which suggested that TFEB should interact with ERRα and be involved in EC lipid reprogramming and progression, which triggered our interest. TFEB downregulation or de ciency can obviously affect the cellular phenotype in a physiologically relevant manner in settings including atherosclerosis 26 , nonalcoholic fatty liver disease 27 , cancer 28 and neurodegeneration 29 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Guo et al suggested that metformin significantly reversed obesity-driven lipid and protein biosynthesis upregulation in an obese LKB1 fl/fl p53 fl/fl mouse model of EC [ 22 ]. Recently, an increasing number of studies have confirmed that ERRα is a key regulator of metabolism in obesity-related tumors, such as breast cancer [ 23 ], prostate cancer [ 24 ], and EC [ 25 ]. Moreover, ERRα-mediated signaling pathways have recently emerged as key factors in the regulation of cancer lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%